Crash Landing: Citizens, The State and Protest Against Federal Airport Development, 1968-1976 - Rowan, Michael (My University, 2019)
Abstract During the 1960s both the federal and provincial governments continued to take on new and larger responsibilities. During this same time period citizens began to mobilize and challenge the state on a number of social issues including race, gender, labour, urban sprawl and the environment. Citizens believed that not only did they have the right to challenge the authority of government in planning public policy, but they also had a right to participate in the decision-making process as much as any bureaucrat, expert, or elected official. In planning airports in Pickering, Ste. Scholastique and Sea Island, the federal government was opposed by citizen groups in each of these three cases. Citizens believed their voices were not being heard and that government officials did not respect them. As a result, they disrupted the meticulously laid out plans of elected officials and policy planners by drawing on evidence and expert advice. The conflict over federal airport development is an example of the evolution of the consultation process with citizens, as citizens challenged the way public policy was planned. Governments now had to justify policies like expropriation for the public good since citizen groups would form over any intrusion into their private lives. The debates over airport planning highlights the role of citizens, bureaucrats, provincial and federal politicians as they all tried to navigate the complex shifting landscape of the Canadian state. By 1976 the Pickering Airport had been canceled, Mirabel was opened, and the Sea Island runway expansion would be delayed for 15 years. Although the citizen groups never had complete victories, citizen participation became more paramount to state planning after these events. Public policy planning in Canada had become far more inclusive than ever before. Whether the politicians, bureaucrats or citizens were aware of the consequences remain to be seen.
Keywords: Airports; Consultation; Prime Minister Trudeau; Mirabel; Pickering; Sea Island; Liberal Party; Regional Development, Expropriation